Dysfunctional Finance : Positive Shocks and Negative Outcomes - Hoff, Karla (2012)
This paper shows how badly a market economy may respond to a positive productivity shock in an environment with asymmetric information about project quality: some, all, or even more than all the benefits from the increase in productivity may be dissipated. In the model, based on Bernanke and Gertler (1990), entrepreneurs with a low default probability are charged the same interest rate as entrepreneurs with a high default probability. The implicit subsidy from good types to bad means that the marginal entrant will have a negative-value project. An example is presented in which, after a positive productivity shock, the presence of enough bad type's forces the interest rate so high that it drives all entrepreneurs out of the market. This happens in an industry in which there are good projects that are productive. The problem is that they are contaminated in the capital market by bad projects because of the banks inability to distinguish good projects from bad. One possible explanation for the lack of development in some countries is that screening institutions are sufficiently weak that impersonal financial markets cannot function. If industrialization entails learning spillovers concentrated within national boundaries, and if initially informational asymmetries are sufficiently great that the capital market does not emerge, then neither industrialization nor the learning that it would foster will occur.